Nematode Management in Kansas: Chemical and Biological Control - Jardine, Douglas J.; Todd, Timothy C. (My University, 1992)
This publication provides information on the chemical and biological control of nematodes.
MF1038_1992_05
Keywords: MF1038; Crops; Pests; MF